(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
Responding to the 2020 COVID-19 pandemic, when news of quarantines, shutdowns, and sheltering-in-place mandates abounded, the organizers of the tenth fashion congress of Ixel Moda in Cartagena, Colombia decided collectively to develop the content for an unprecedented five-day, 3-dimensional virtual gathering that would bring together artisans, designers, chefs, scholars, and other creators. The event would provide the scenario for exchanges on many facets of culture—food, music, film, fashion, politics, museum exhibits, performance, decorative arts, sustainability, tourism, and advertising—in the midst of a difficult period. This essay explores Ixel Online 2020 as a showcasing of the creative arts, includes the voices of the cultural organizers, and proposes this event as a model for increased international dialogue in the face of global crisis.